Pre-service English teachers’ reflective practice via online journaling during school-based teaching internship program at the time of Covid-19 pandemic - Al Arthur Irfan Fauzi; Irma Astuti (Universitas Islam Malang, 2023)
This study explores the reflective practices of two pre-service English teachers (PSETs) during their school-based teaching practice and internship program at the time of Covid-19. The purpose of this research is to describe PSETs reflections during their online school-based teaching practicum. The data were collected by utilizing the research participants’ journal writing as part of their e-portfolio projects which they kept during the teaching practicum. The collected data were analyzed thematically referring to Bain, Ballantyne, Packer & Mills, (1999). The research revealed four main thematic findings namely, Focus on Teaching, Focus on Self, Focus on Professional Issues, and Focus on Students or Class. Furthermore, the study also identified frequent sub-themes, such as General Teaching Issues (GTI), Specific Lessons or Incidents (SI), Own Teaching Approach (OTA), Relationship/Discussion with Supervising Teaching (RST), Teaching as Profession (TP), Professional Preparation (PP), Student /Class Behavior (SBC), Student /Class Characteristics (SCC). Overall, this research suggests that the use of online journaling helps to facilitate the reflective practices of prospective future English language teachers introspecting on a multitude of aspects of their teaching practicum/ internship program.